A case-study on the mechanism of flank wear during laser-assisted machining of a titanium alloy. (2017) - Rashid, R.A. Rahman; Palanisamy, Suresh; Sun, Shoujin; Dargusch, M.S.
In recent years, researchers have been investigating various technologies including laser-assisted machining (LAM) to improve the machinability of titanium alloys which is considered to be one of the difficult-to-cut materials. The LAM process involves heating the titanium workpiece with a laser beam of sufficient power to soften the material before it engages with the cutting tool. Benefits of LAM include significant reduction in cutting forces as well as better surface finish. However, as diffusion wear is the most dominant tool wear mechanism associated when machining titanium alloys, the effect of the additional heat from laser preheating on the cutting tool life is not clearly understood. Therefore, this paper aims at investigating the tool life of an uncoated carbide tool during LAM of Ti-6Al-4V alloy, as well as identifying the principal flank wear mechanisms involved during the cutting process. It was found that the tool life was reduced by about 8% when machining the workpiece with laser preheating. Moreover, it was found that the carbon from the cutting tool diffused into the titanium built-up edge formed in the vicinity of the cutting zone from where it was carried out through the chips. This considerably weakened the cutting edge of the tool resulting in accelerated tool wear.